Effect of ionizing radiation on MOS capacitors - Chauhan R.K.; Chakrabarti P. (My University, 2025)
A numerical model of metal-oxide-semiconductor (MOS) capacitor has been developed to investigate the effect of ionizing radiation on the characteristics of the device during exposure and also in the post-irradiated condition. The model takes into account the effect of radiation-induced changes in silicon-dioxide as well as in silicon substrate of MOS structure. It is found that the total high frequency capacitance of the device during exposure to radiation is different from its value in the post-irradiated condition. The results of the study are expected to be useful in predicting the behavior of MOS based devices operating in radiation environment. © 2002 Published by Elsevier Science Ltd.